China and Falun Gong: Party and society relations in the modern era - Leung, Beatrice (Journal of contemporary China, 2002)
This article aims at giving an in-depth analysis on Falun Gong through a discussion of the determining and underlying reasons behind the phenomenon. From a political-sociological perspective, Falun Gong is taken as a quasi-religion which was able to function, first under political disapproval and then under severe legal constraints, thanks to a combination of modern day communication technology, indigenous Chinese culture and changes in state/Party and society relations. (J Contemp China/DÜI)